FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN TUMBUH KEMBANG ANAK USIA 1 – 3 TAHUN DI DESA KAYU LAUT KECAMATAN PANYABUNGAN SELATAN KABUPATEN MANDAILING NATAL TAHUN 2020 - Lubis, nurkholidah (Universitas Aufa Royhan, 2020)
Growth is a measure of physical maturity. It is characterized by an increase in the size of the body and its different organs and development is an increase in the ability to structure and function more complex bodies in a regular pattern. According to UNICEF in 2005, data was obtained that the incidence of growth and development disorders in children under five, especially motor development disorders, was obtained 23.5% / 5 million children experiencing disorders. The purpose of this study was to determine the factors associated with the growth and development of children aged 1 - 3 years in the village of Kayu Laut. This research is an analytical observation using a cross-sectional design, is descriptive by distributing questionnaires and by using accidental sampling, with the number of sample of 95 respondents. The results of the research conducted in the village of Kayu Laut, South Panyabungan District, Mandailing Natal Regency, were obtained based on the sex of the majority of the female gender as many as 59 people (41.1%) male gender minority as many as 36 people (37.9%) based on the order of the children. majority order 1-2 as many as 48 people (50.5%) minority order> 2 as many as 47 people (49.5%) based on poor nutritional status as many as 58 people (61.1%) good minority as many as 37 people (38.9 %) based on the majority of incomplete immunization status as many as 77 people (81.1%) complete minority as many as 18 people (18.9%) based on the socioeconomic status of the majority as many as 83 people (87.4%) high minority as many as 12 people (12 , 6%) based on parenting style, the majority of bad supervision were 74 people (77.9%) minority good supervision was 21 people (22.1%) based on the community, the majority of the community was healthy, as many as 65 people (68.4%), the minority was unhealthy as many as 30 people (31.6%) The results of research on 95 children aged 1-3 years, the factors that influence children's growth and development are immunization status with p-value = 0.023 and parenting with p-value = 0.034, the most dominant variable affecting children's growth and development is parenting. , it is suggested for the public to always pay attention to the growth and development of their children to produce good, smart, healthy and intelligent children